Aberrantly plumaged orioles from the Trans-Fly savannas of New Guinea and their ecological and evolutionary significance. (3rd July 2019) - Joseph, Leo; Dolman, Gaynor; Iova, Bulisa; Jønsson, Knud; Campbell, Catriona D.; Mason, Ian; Drew, Alex
ABSTRACT: Two species of orioles, namely the Olive-backed Oriole ( Oriolus sagittatus ) and the Yellow Oriole ( O. flavocinctus ), occur across northern Australia. In New Guinea, both are confined to the Trans-Fly region immediately north of Cape York Peninsula. They occur there in Melaleuca -dominated 'swamp savanna', which is neither eucalypt savanna nor rainforest typical of their Australian habitats. A readily identifiable specimen of the Olive-backed Oriole collected in 2014 from the Trans-Fly has a mitochondrial DNA ND2 haplotype identical with Yellow Orioles. Its dorsal plumage has traits typical of Yellow Orioles. We infer it to have been descended from a hybridisation event involving a female Yellow Oriole followed by successive generations of backcrossing with Olive-backed Orioles. Three aberrantly plumaged orioles from New Guinea's Trans-Fly region date from 1937, 1969 and 2014. The 1969 specimen appears to be an aberrant Yellow Oriole. Molecular data are similarly not available for the 1937 specimen but its plumage is suggestive of hybrid origin. The 2014 bird's ND2 haplotype is identical with some Olive-backed Orioles and is inferred to be descended from hybridisation involving a female Olive-backed Oriole. Integration of phenotypic and genetic data directs study to understand drivers underpinning an unusually high frequency of aberrantly plumaged orioles.